2019
DOI: 10.1371/journal.pone.0217319
|View full text |Cite
|
Sign up to set email alerts
|

The causal nexus between energy consumption, carbon emissions and economic growth: New evidence from China, India and G7 countries using convergent cross mapping

Abstract: Understanding the causality between energy consumption, carbon emissions and economic growth is helpful for policymakers to formulate energy, environmental and economic policies. For the first time, based on nonlinear dynamics, this paper employs multispatial convergent cross mapping (CCM) to revisit the energy-carbon-economy causation for China, India and the G7 countries using both aggregate data and per capita data. The findings indicate that there are significant differences between developing countries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 41 publications
(60 reference statements)
4
28
0
Order By: Relevance
“…In the Congo Republic, Kenya, Nigeria, Zambia, Italy, Japan, and the UK, electric consumption Granger causes carbon emissions. In Japan and the UK, the results reveal a unidirectional causality running from economic growth to carbon emission consistent with the results of [22] who reported a unidirectional causality between economic growth and carbon emission in Japan. A unidirectional causality is running from economic growth to electric consumption in the Congo Republic and Japan.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the Congo Republic, Kenya, Nigeria, Zambia, Italy, Japan, and the UK, electric consumption Granger causes carbon emissions. In Japan and the UK, the results reveal a unidirectional causality running from economic growth to carbon emission consistent with the results of [22] who reported a unidirectional causality between economic growth and carbon emission in Japan. A unidirectional causality is running from economic growth to electric consumption in the Congo Republic and Japan.…”
Section: Discussionsupporting
confidence: 89%
“…Over the years, many researchers have investigated the nexus between energy consumption, carbon emissions, and economic growth, without a consensus. Due to the mixed results, many countries have been put in a difficult situation when formulating and adopting energy policies [22]. The diversity in recent findings is as a result of the different methodologies applied, the different time frames, and diverse countries studied according to [23].…”
Section: Panel Unit Root Tests Panel Cointegrationmentioning
confidence: 99%
“…These energy sources not only provide power but play a key role in increasing carbon emissions. Fossil fuel per capita and energy consumption cause to increase in carbon emission (Huang, Krigsvoll et al 2018;Ahmed and Shimada 2019;Liu, Lei et al 2019). Therefore, due to the detection of energy and fuel as well as green and sustainable technology reveals that scholars need to pay attention more to research green and sustainable technology for a sustainable environment.…”
Section: Cloud Energy and Fuelmentioning
confidence: 99%
“…The International Panel on Climate change defines climate change as the significant change in climate variables (rainfall and temperature) of a given location over a given period [ 19 ]. Climate change has for a very long time been a global issue with many experts linking the cause to human-factors [ 20 ]. Hertwich and Peters [ 21 ] showed that daily household consumption and production decisions contributed to about 72% of global emissions.…”
Section: Literature Reviewmentioning
confidence: 99%